An exploratory factor analysis on the open and distance learning among university students during the COVID-19 pandemic in Malaysia / Nor Hamiza Mohd Ghani ... [et al.] - Mohd Ghani, Nor Hamiza; Abdullah, Sholehah; Ismail, Mohd Khairi; Ahmad, Noorazlina; Affandi, Salwani; Mohamad Azmin, Nur Azwani; Abdul Manaf, Suhaily Maizan (Universiti Teknologi MARA, 2022)
Numerous educational institutions worldwide have halted face-to-face teaching and learning sessions in response to the COVID-19 outbreak. In Malaysia, the suspension began in March 2020, pushing educational institutions to transition to online classrooms and reshape their academic calendars for consecutive semesters. The reality of online classes necessitates a discussion about a new pedagogical work in which students and educators must understand how to manage online learning and make the most of online technologies. To do so, students must first gain an understanding of the difficulties inherent in open and distance learning (ODL). From the perspective of students, this article examines the difficulties associated with online learning during the COVID-19 pandemic. As a sample, 495 students from UiTM Terengganu who were actively engaged in online learning activities were included in this study. In this study, Exploratory Factor Analysis (EFA) was used to analyse the data in order to determine which factors contributed to ODL challenges faced by UiTM Terengganu students. Findings showed, the most significant challenges for the majority of students are technology and the internet. Additional concerns raised included interaction between students and lecturers, psychological issues, difficult assessments, and self-management. The significance of the study is that the university can take the initiative to address the primary challenges faced by students thereby increasing the effectiveness of ODL in the future.